2012
DOI: 10.1111/j.1460-9568.2012.08176.x
|View full text |Cite
|
Sign up to set email alerts
|

Increases of corticospinal excitability in self‐related processing

Abstract: Involvement of fronto-parietal structures within the right hemisphere in bodily self recognition has gained convergent support from behavioural, neuropsychological and neuroimaging studies. Increases in corticospinal excitability via transcranial magnetic stimulation (TMS) also testify to right hemisphere self-related processing. However, evidence for self-dependent modulations of motor excitability is limited to the processing of face-related information that, by definition, conveys someone's identity. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…These showed 1) the subject's own hand, 2) the hand of another human subject, 3) the subject's own mobile phone, or 4) the mobile phone of another person. Interestingly, Salerno et al (2012) observed similar neurological responses when subjects were presented with images of both their own hands and their own mobile phones (i.e., self-related stimuli). However, these responses were distinct from those elicited by the images of 'other-related' stimuli (i.e., the hands or phones of other people).…”
Section: Embodied Cognitionmentioning
confidence: 77%
See 4 more Smart Citations
“…These showed 1) the subject's own hand, 2) the hand of another human subject, 3) the subject's own mobile phone, or 4) the mobile phone of another person. Interestingly, Salerno et al (2012) observed similar neurological responses when subjects were presented with images of both their own hands and their own mobile phones (i.e., self-related stimuli). However, these responses were distinct from those elicited by the images of 'other-related' stimuli (i.e., the hands or phones of other people).…”
Section: Embodied Cognitionmentioning
confidence: 77%
“…However, these responses were distinct from those elicited by the images of 'other-related' stimuli (i.e., the hands or phones of other people). Although the psychological significance of these results is unclear at the present time, Salerno et al (2012) note that issues of bodily extension may be relevant to their findings. Interestingly, the effects observed by Salerno et al (2012) were specific to the right hemisphere of the brain.…”
Section: Embodied Cognitionmentioning
confidence: 85%
See 3 more Smart Citations